Experimental treatment with sodium stibogluconate of hamsters infected with Leishmania (Leishmania) chagasi and Leishmania (Leishmania) amazonensis - Elizabeth M. de Figueiredo; Jaime Costa e Silva; Reginaldo P. Brazil (Revista da Sociedade Brasileira de Medicina Tropical, 1999)
The present paper reports the experimental treatment of hamsters infected with Leishmania chagasi and Leishmania amazonensis with sodium stibogluconate (20mg/kg/day x 20 days). Only with L. chagasi did the treatment result in the complete elimination of parasites from the spleen. However, no parasitological cure was achieved in hamsters infected with L. amazonensis.